2022
DOI: 10.1007/s10072-022-06237-y
|View full text |Cite
|
Sign up to set email alerts
|

Human tissue lead (Pb) levels and amyotrophic lateral sclerosis: a systematic review and meta-analysis of case–control studies

Abstract: Aim To combine the current scientific literature evidence and elucidate the differences of lead (Pb) bioaccumulation in human tissues by comparing amyotrophic lateral sclerosis (ALS) patients and healthy controls. Methods We systematically searched for case–control studies on the association of Pb levels with ALS, in human cells, tissues, and body fluids (nervous tissue, muscle, blood, cerebrospinal fluid, urine, skin appendages). Then, we performed a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Case-control studies found higher Pb levels in ALS cases than controls in blood from a statistical view. However, statistically significant results were not observed for tissues like plasma/serum and cerebrospinal fluid (CSF) ( [ 5 ]). It has been proved that Pb tended to accumulate inside the erythrocytes rather than into the plasma component ( [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies found higher Pb levels in ALS cases than controls in blood from a statistical view. However, statistically significant results were not observed for tissues like plasma/serum and cerebrospinal fluid (CSF) ( [ 5 ]). It has been proved that Pb tended to accumulate inside the erythrocytes rather than into the plasma component ( [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Pb associated with several neurodegenerative diseases, like ALS, Alzheimer’s disease (AD), Parkinson’s disease (PD) ( [ 4 ]). A meta-analysis of 14 case-control studies found statistically higher Pb levels in ALS cases than controls in whole blood samples ( [ 5 ]). Our unpublished data provided novel evidence that Pb caused abnormal aggregation of SOD-1 in motor neurons by interfering with the chaperone functions of Glucose-Regulated Protein of 78 kDa (GRP78).…”
Section: Introductionmentioning
confidence: 99%
“…Metals are introduced into the environment as mixtures from various anthropogenic sources such as mining, refining, the smelting of ores, or agriculture and natural activities [1,2]. The exposure of human beings to arsenic (As), lead (Pb), and manganese (Mn) through water and foods has raised increasing concerns about health risks [3][4][5]. The interactions of metals in these mixtures can influence their uptake and deposition in organs, which may eventually amplify the overall toxicity in exposed organisms [6][7][8].…”
Section: Introductionmentioning
confidence: 99%